O desafio de formar formadores na e para a educação tecnológica: o método misto de pesquisa para análise dos saberes e da aprendizagem docente no contexto das tecnologias de informação e comunicação - Gravonski, Isabel Ribeiro (2013)
Numerous studies have been developed on the importance of technology in education, specifically how informatics can assist in the teaching and learning process. The Information and Communication Technologies (ICTs) differ from many other educational resources, since besides its tool benefits; it allows greater access to knowledge and fosters new spaces of interaction. However, educational professionals need to take more advantage to further exploit these technologies in the classroom, since the digital technology requires more than technical knowledge of the tool. The aim of the present study was to analyze how teachers who teach in undergraduate courses for teacher education learn to train teachers for the context of information and communication technologies. This study is justified by the need to look back to the teaching practice on higher education in order to identify how those professionals are learning to be teachers, and what interference technologies are exerting on the preparation of new teachers. The methodology used was the exploratory sequential mixed design that blends qualitative and quantitative approaches in research. In the qualitative approach, the first phase of the study, a multifocal analysis was performed through documents and semi-structured individual interviews. The institutional documents analyzed were the Institutional Educational Project of a state university in Paraná and the curricula of their undergraduate for teaching education courses. In addition to these documents, observations of reports of an institutional event were performed as well. For the interview were chosen intentionally ten (10) teachers who were part of a discussion group about the undergraduate for teaching education courses. From the results of this phase, it was developed an instrument to collect data for the second phase. In this second phase of the study, quantitative, the questionnaire was validated by doctors, tested in a pilot study and ultimately administered to a sample of 143 teachers representing all undergraduate for teacher education courses of the institution. In addition to identifying and measuring teacher knowledge and use of ICT in their courses, the main results of the study were: the valorization of practice in teacher education and teaching with research as characteristic of Technological Education, recognition of the importance of the teaching experience on using information and communication technologies as educational technologies, and, finally, with the integration of the results obtained in the two study phases, it was possible to characterize teacher learning as the result of interactive practices mediated by shared experiences in communities.